Fuzzy Logic Based Incubator Temp And Humid Level Controller Prototype - Kuat Supriyadi (Journal of Telematics and Informatics, 2020)
Younger babies born with low body weight are increasingly critical and at risk for these babies. To overcome this problem, we need a device of medical equipment that can replace uterine function, whose condition is like that of a baby still in the womb of his mother. Temperature, humidity, oxygen, sound and light levels for the development of the most suitable low birth weight babies. Not only the temperature, humidity and noise factors that must be considered, but also pay attention to other problems that can interfere with baby's health, among others; Factors such as skin that directly contact family members also contribute to disease in infants, because baby's skin is still very sensitive, and has the potential to become infected. Babies with very low birth weight have a very high risk, especially when they feel cold. When a baby experiences heat loss, creating a physiological response that exceeds that of a normal baby, physiological balance will be severely disrupted, this is because the baby needs to expend energy and metabolize oxygen to produce its own heat. The purpose of using an incubator is to create a very stable environment so that the birth of a baby with a low body weight can maintain a constant body temperature. In designing the incubator must pay attention to the condition of the humidity in the chamber, for the sensitivity of the chamber temperature is relatively easier but if the conditions of dry humidity will greatly affect the health of the baby. Ideal moisture loss will cause transepidermal water loss (TEWL) in premature infants. From the results of the Overall System Measurement and Research conducted in RSUP Dr. Sarjito on April 23, 2019. This location was chosen because the place has a temperature, humidity and noise level that is stable enough so that it is suitable for the location of the baby incubator.